Neuroendoscopic Biopsy of Brain Lesions; Accuracy and Complications (Medical Forum Monthly, 2020)
Objective: To assess the accuracy of neuroendoscopic biopsy of brain lesions and complications associated with it.Study Design: Retrospective study.Place and Duration of Study: This study was conducted at the Department of Neurosurgery, Nishtar Hospital Multan from January 2010 to March 2020.Materials and Methods: There were 347 cases of neuroendoscopic processes performed in different patients during a period of almost 10 years. We selected 40 patients with intra-ventricular or periventricular lesions according to the database present and obtained the biopsy samples from these patients. Only life threatening complications were taken into account. Bleeding was considered as major complication that leads to execution of the procedure, requirement of unplanned EVD insertion or if detected postoperatively cause further surgery. All the data was subjected to statistical analysis with the help of computer software SPSS version 23. Frequency and percentages were calculated for categorical variables while mean and standard deviation was calculated for continuous variables.Results: Total 33 (82.5%) samples were accurately diagnosed as 12 of these were reconfirmed by new sample, 13 patients’ diagnoses showed compatibility with the ongoing treatment, and diagnosis of 8 patients was compatible with the follow up. Total 5 (12.5%) samples were inaccurately diagnosed as new biopsy results varied in 3 patients, clinical course was nor aligned with the diagnosis in one patient and indecisive findings were observed in one patient. Of 40 biopsies, 38 samples were included in complete study because one patient died and one patient lost follow up.Conclusion: The results of our study show that the use of the new method to assess the accuracy of endoscopic biopsy revealed high accuracy in diagnostic biopsy.